2012
DOI: 10.1200/jco.2012.30.15_suppl.9552
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of diet and physical activity to metabolic parameters among survivors of childhood leukemia.

Abstract: 9552 Background: Survivors of childhood acute lymphoblastic leukemia (ALL) are at increased risk for obesity, insulin resistance and increased visceral adiposity. A history of cranial radiation therapy (CRT) worsens this risk. In non-cancer populations, adherence to a Mediterranean Diet has been shown to improve metabolic parameters and risk of diabetes mellitus. Whether diet may contribute to insulin resistance and increased adiposity in ALL survivors is not known. Methods: We surveyed 117 adult survivors of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 40 publications
3
7
2
Order By: Relevance
“…We found a mean HEI‐2010 of 52.7 in 22 CCS, similar to the mean HEI‐2005 score of 55.5 in a previous study of 91 CCS (mean age = 19 years), which assessed adherence to the 2005 DGA . Prior studies, although used different indices and assessment methods to capture nutritional intake, have consistently reported poor diet quality in CCS . The mean diet quality score was either less than half or only slightly above half of the maximum score , ranging from 33% to 56%.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…We found a mean HEI‐2010 of 52.7 in 22 CCS, similar to the mean HEI‐2005 score of 55.5 in a previous study of 91 CCS (mean age = 19 years), which assessed adherence to the 2005 DGA . Prior studies, although used different indices and assessment methods to capture nutritional intake, have consistently reported poor diet quality in CCS . The mean diet quality score was either less than half or only slightly above half of the maximum score , ranging from 33% to 56%.…”
Section: Discussionsupporting
confidence: 82%
“…Prior studies, although used different indices and assessment methods to capture nutritional intake, have consistently reported poor diet quality in CCS . The mean diet quality score was either less than half or only slightly above half of the maximum score , ranging from 33% to 56%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As observed in the general population, engaging in risky or suboptimal health behaviors has implications for the overall health of survivors. For instance, survivors with better diet quality have lower adiposity, waist circumference, and body mass index; whereas those with poor diet have an excess risk of conditions associated with the metabolic syndrome . Similarly, compared with inactive survivors, those with higher rates of physical activity are more likely to have lower fat mass, abdominal visceral fat, and waist circumferences .…”
Section: Health Behaviorsmentioning
confidence: 99%
“…The authors observed that females, adolescence and young adults, and survivors of tumors of the central nervous system or lymphoma may be at higher risk of following poor dietary patterns than other groups of survivors. Tonorezos et al reported that with greater adherence to the Mediterranean diet, the odds of developing metabolic syndrome fell by 31% (odds ratio 0.69; 95% CI 0.50-0.94; p = 0.019), 27 lending preliminary support for the role of dietary behaviors for the prevention of late effects of childhood cancer. Other cross-sectional surveys have reported positive associations between adherence to dietary recommendations and a higher frequency of physical activity, suggesting that healthy dietary behaviors may also promote the adoption of other healthy lifestyle behaviors.…”
Section: Lifestyle Interventions (Diet and Physical Activity)mentioning
confidence: 99%